2013
DOI: 10.1103/physreve.87.053010
|View full text |Cite
|
Sign up to set email alerts
|

Elongational flow effects on the vortex growth out of Couette flow in ferrofluids

Abstract: The growth behavior of stationary axisymmetric vortices and of oscillatory, nonaxisymmetric spiral vortices in Taylor-Couette flow of a ferrofluid in between differentially rotating cylinders is analyzed using a numerical linear stability analysis. The investigation is done as a function of the inner and outer cylinder's rotation rates, the axial wave number of the vortex flows, and the magnitude of an applied homogeneous axial magnetic field. In particular, the consequences of incorporating elongational flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, for a symmetry breaking (e.g., transverse), magnetic field such linear stability analysis is not known for the corresponding basic state at such a field configuration. For a detailed description regarding the linearization around the CCF and solution of the linearized NSE, we refer to the Appendix in [43].…”
Section: Linear Stability Behavior and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, for a symmetry breaking (e.g., transverse), magnetic field such linear stability analysis is not known for the corresponding basic state at such a field configuration. For a detailed description regarding the linearization around the CCF and solution of the linearized NSE, we refer to the Appendix in [43].…”
Section: Linear Stability Behavior and Analysismentioning
confidence: 99%
“…Reindl et al [9] also observed hysteresis between vortex flows with different k when increasing and decreasing the Reynolds numbers Re 1 . The bifurcation thresholds ( Figure 11 ¼ 0 ðÞ is considered in the linearized ferrofluid equations [43]. Right column of Figure 11(2) presents the wavenumber dependence of the corresponding marginal spiral frequencies at the onsets for m ¼ 1SPI.…”
Section: Axial Wavenumber Dependencementioning
confidence: 99%
“…The basic idea consists of supposing that the ferrofluid in which the microbeads are dispersed may undergo a field-induced structuring manifested by the appearance of nanoparticle chains or droplike elongated aggregates extended along the direction of the applied magnetic field [15,31,32]. FIG.…”
Section: A General Frameworkmentioning
confidence: 99%
“…A theoretical and experimental investigation on the Dean problem of ferrofluids has not gained much attention, though, a significant research work has been done in the parallel problem on the instability of the circular Taylor-Couette ferrofluid flow between concentric rotating cylinders with axial magnetic field [17][18][19][20][21][22][23][24][25][26][27][28]. Some work on mixed convection of ferrofluid in a curved tube has also been reported recently by Aminfar et al [29], where an enhancement of the heat transfer is observed numerically in the presence of externally applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%